The Effect of Earth Rotation Diorama Learning Media on the Critical Thinking Ability of Science Subjects in State Elementary School - Ritonga, Yunizar; Zunidar, Zunidar (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to investigate the influence of Earth Rotation Diorama learning media on the critical thinking ability of grade VI students in elementary school. This study uses a quantitative method with a quasi-experimental design. All participants in this study were students in grade VI of SD Negeri No 060909 Medan Denai. The data collection technique was carried out using research instruments in the form of questionnaires on the validity of questions and tests (pretest and posttest). The sampling technique in this study uses simple random sampling, with the sample used being 15 grade VI students who are divided into control groups and experiments groups to be given a pretest and a posttest. The data analysis is quantitative or statistical through validity, realism, difficulty level of questions, differentiation, data normality, homogeneity, and hypothesis test calculated using SPSS version 30. From this study, the results were obtained, from the posttest showed that the experimental class exceeded the control class. Students' critical thinking skills are tested at a real level = 0.05. Tallahassee (∝> 0, 855 > 0, 514). And the significant rate is 0.001 to 0.05. The data normality test showed that the pretest < posttest in the control class with a sig of 0.067, 0.05, and the experimental class with a sig of 0.144, 0.05, showed that the data followed a normal distribution. Because the results of the hypothesis test are less than 0.05, it can be concluded that the use of Earth Rotation Diorama media has proven to be efficient in improving critical thinking skills.